Adenosine triphosphate induced transition-metal phosphide nanostructures encapsulated with N, P-codoped carbon toward electrochemical water splitting. (1st May 2023) - Wei, Peng; Sun, Xueping; He, Zhimin; Cheng, Fangyuan; Xu, Jia; Li, Qing; Ren, Yurong; He, Jianhua; Han, Jiantao; Huang, Yunhui
Graphical abstract: A universal and scalable synthetic strategy is proposed to prepare various N, P co-doped carbon-encapsulated transition metal phosphide nanostructures (TMP@NPCs) employing green and low-cost adenosine triphosphate (ATP) as a novel phosphorus source. Highlights: Adenosine triphosphate as a novel green phosphorus source is reported. Various nano-sized metal-rich phosphides embed N, P doped carbon are synthesized. The Co2 P@NPC exhibits excellent catalytic activity and durability for HER and OER. The sequence of HER activity of various phosphides is verified by DFT. Water electrolysis measurement also shows excellent electrochemical performance. Abstract: Transition metal phosphides (TMPs) have emerged as the most potential non-precious metal catalysts thanks to their high abundance, low cost and superior catalytic activity. Although numerous efforts have been devoted to gain TMPs, most of the synthetic processes are dangerous and complex as the utilization of flammable and toxic phosphorus sources. By using a novel green phosphorus source-adenosine triphosphate (ATP), we synthesized various N, P doped carbon-sealed TMPs nanostructures (TMPs@NPC) via a facile and simple solid-phase method. Benefiting from the porous nanostructure and in situ derived heteroatom-doped carbon encapsulation, as-synthesized TMPs@NPC exhibit good bifunctional catalytic performance. Notably, the Co2 P@NPC demonstrates the superior activity and durability toward HER and OER. The Co2 P@NPC, meanwhile, displays robust overall water electrolysis performance. Therefore, our work presents a simple, ecofriendly, and general strategy for the synthesis of TMPs encapsulated with N, P-codoped carbon nanostructures, which are also expected to show a bright future in other electrochemical applications.